2014
DOI: 10.7899/jce-13-34
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three different methods of distance learning for postgraduate diagnostic imaging education: A pilot study

Abstract: Objective: The purpose of this study was to evaluate the perceived effectiveness and learning potential of 3 Web-based educational methods in a postgraduate radiology setting. Methods: Three chiropractic radiology faculty from diverse geographic locations led mini-courses using asynchronous discussion boards, synchronous Web conferencing, and asynchronous voice-over case presentations formatted for Web viewing. At the conclusion of each course, participants filled out a 14-question survey (using a 5-point Like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…On the other hand, factors that negatively impact change include resistance, behavior change, balance between different tasks, lack of involvement, lack of consensus, and unsafe culture and hierarchy [ 7 , 13 , 41 ]. Therefore, technological approaches to postgraduate medical education such as e-learning, web-based teaching, social media and artificial intelligence are necessary to assuage key intrinsic and extrinsic factors driving radiologists desire for personal professional development [ 24 , 36 , 39 ]. Key intrinsic factors included desire for personal professional development, desire for new challenges and search for satisfaction within the profession [ 19 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, factors that negatively impact change include resistance, behavior change, balance between different tasks, lack of involvement, lack of consensus, and unsafe culture and hierarchy [ 7 , 13 , 41 ]. Therefore, technological approaches to postgraduate medical education such as e-learning, web-based teaching, social media and artificial intelligence are necessary to assuage key intrinsic and extrinsic factors driving radiologists desire for personal professional development [ 24 , 36 , 39 ]. Key intrinsic factors included desire for personal professional development, desire for new challenges and search for satisfaction within the profession [ 19 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…With this asynchronous model, modules or lecture videos given by lecturers can be accessed anytime and anywhere as needed through platforms such as YouTube and Google Classroom, and even students are free to access various other sources. The asynchronous model gives students tremendous flexibility to study online material at their convenience and own pace, even discussing in small groups using blog platforms or email (Asabere et al, 2017;Poirier et al, 2014;Polat & Kayaduman, 2022;Rao, 2011). Of course, lectures with this model can save costs, mainly student internet quotas.…”
Section: Synchronous and Asynchronous Lecturesmentioning
confidence: 99%
“…It has been reported that web conferencing produced equivalent learning outcomes when compared to F2F learning, though this was evaluated through an observational case study [6]. Others have compared web conferencing to asynchronous text-based lectures or discussion boards [12,13]. In regard to web-based CBL, Crawford [8] reviewed six qualitative investigations into web-based CBL and concluded learning that utilizes computers may complement the current CBL learning experience.…”
Section: Introductionmentioning
confidence: 99%